The Effect of the High-Intensity Interval Training Program in Increasing VO²max Capacity and Heart Rate Recovery - Subekti, Nur; Raihan, Amar Abdullah Dani Arni; Hafif, Muhammad; Syaukani, Agam Akhmad (Faculty of Sport and Health Sciences, 2022)
This research aims to test the effects of the program High-Intensity Interval Training (HIIT) on VO2max capacity and heart rate recovery. A total of 13 student-level Pencak Silat athletes met the conditions set out in this study, namely: (fighting category athlete, male, age 19.5±1.4 years, and actively practicing = 4.9±0.9 years). Experimental procedures by design one group pretest-posttest applied for 4 weeks, where data was taken for each subject before and after training using the procedure Yo-yo Intermittent Recovery Test Level 1 (YYIR1) and monitoring heart rate recovery with the heart rate monitor Polar-H10 on the HIIT protocol work: rest ratio (1:1). Data from all subjects was processed using the SPSS tool, where the hypothesis testing process was carried out using prerequisite tests. The results showed a significant increase (p<0.05) in VO2max capacity (2.9 ± 1.4 ml.kg-1.min-1) and heart rate recovery (9.8±9.1). With increasing VO2max given heart rate recovery it can be concluded that the HIIT program has proven to be effective in increasing aerobic ability and a faster recovery process, so that it will support more optimal athlete performance.